Job Satisfaction, Job Fairness, and Job Evaluation as an Initial Step of Reward Management System Development: The Implementation of Quality of Work Life Concept - Laurentia Verina Halim Secapramana; Heidi Patricia; Eko Nugroho (APMBA (Asia Pacific Management and Business Application), 2019)
Quality of work life is an important concept that determines happiness in human life as well as job satisfaction that supports to increased motivation, organizational commitment, and work productivity. One factor that affects the level of job satisfaction is job fairness. Distributive and procedural justice are strong predictors of the fairness felt by employees. The intervention aims to increase fairness and job satisfaction through job evaluations that produce job grading as the beginning of the reward management system. This intervention is also an implementation of the concept of quality of work life that will be applied in the company. This study applies an action research using quantitative and qualitative methods at the same time (mix-method). A total of 79 job holders in 13 divisions at a head office became participants. In the pre-assessment stage, measurement of quality of work life is carried out, in the assessment stage, job satisfaction and job fairness measurements are taken. The results revealed that in the intervention stage a job description is reviewed as part of the job analysis and job evaluation using the Hay method to produce job grading can significantly increase the mechanisms of rewards system. Theoretical and practical implications are discussed.